The occurrence of the genus Calydus Reitter, 1896 (Coleoptera, Meloidae) in Afghanistan with the description of a new species - Shapovalov, Andrey M.; Skrylnyk, Yuriy E. (Zootaxa, 2023)
Calydus yaroslavi new species is described from Central Afghanistan, Bamian Province, Bande-Amir National Park. The genus Calydus Reitter, 1896 is recorded for Afghanistan for the first time.